Influence of gas carburization on the microstructure, mechanical properties, and alloying elements behaviour in plain and alloyed low carbon steels - Krishnamurthy D Ambiger; Murthy B R N; Pavan Hiremath; Shivamurthy R C; Suhas Kowshik; Nithesh Naik; Prateek Jain; H S Arunkumar (Materials Research Express)
This study investigates the effects of gas carburization on the microstructure, chemical composition, and mechanical properties of EN3, 20MnCr5, and EN353 steels. Carburization, performed through boosting, diffusion, and equalization phases, significantly increased surface carbon content, forming a hardened case layer while retaining a softer core. Microstructural analysis revealed coarse pearlite in EN3, fine carbide precipitates in 20MnCr5, and a bainitic matrix enriched with chromium and nickel in EN353. Tensile testing showed an approximately 2% strength increase with a 26% reduction in elongation, where EN3 gained strength through carbon enrichment, while 20MnCr5 and EN353 exhibited greater improvements due to carbide formation and alloying effects. Hardness testing confirmed a around 25.4% increase across all grades, with EN353 achieving the highest case hardness due to its alloying elements. Charpy impact tests indicated a nearly 73% reduction in energy absorption after carburization, attributed to increased brittleness from cementite and carbide formation. These findings highlight the role of alloying elements and carburization parameters in optimizing steels for industrial applications, providing novel insights into microstructural evolution, wear resistance, and the balance between strength and ductility.